Effect of medication adherence on the risk of cardiovascular events in outpatients with stable coronary artery disease: results of two-year monitoring - Fitilev, S. B.; Vozzhaev, A. V.; Saakova, L. N.; Bondareva, I. B.; Kliuev, D. A.; Shkrebniova, I. I. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2023)
Introduction. Incidence of inadequate medication adherence to secondary prevention medications among Russian coronary patients is around 50 %, but the question, how this might influence on the risk of unfavorable outcomes, still has no answer. Aim. To determine the effect of medication adherence on the risk of unfavorable clinical outcomes in outpatients with stable coronary artery disease (CAD). Methods. Prospective observational cohort study was conducted. 281 subjects with verified stable CAD were included in line with the pre-specified criteria. Medication adherence was measured by validated 8-item Morisky scale. Data on cardiovascular events were obtained over the 24-month monitoring period. Study endpoint was a composite cardiovascular event (all-cause mortality, acute myocardial infarction, unstable angina, revascularization surgery, acute heart failure, decompensation of chronic heart failure). Survival analysis by Kaplan — Meier method was performed. Results. 26.0 % of coronary outpatients had low medication adherence (below 6 points by Morisky scale). Groups of patients with satisfactory and low medication adherence were comparable by demography, medical history, and pharmacotherapy. Over the monitoring period composite cardiovascular event was registered in 115 patients (40.9 %). 46.6 % of patients from the low adherence group suffered from the composite event, 38.9 % — from the satisfactory adherence group. Time to the event was lower in the low adherence group — median 24.2 (IQR 7.5-29.2) vs. median 27.9 (IQR 17.4-34.5) months. Cumulative incidence of the composite cardiovascular event over the monitoring period was higher in the low adherence group compared to satisfactory adherence group (p=0.032; log-rank test), also when adjusted for history of cardiovascular events ( p =0.033; log-rank test). Satisfactory medication adherence reduced risk of composite cardiovascular event by 37 % (HR 0.63; 95 % CI 0.42-0.94; р =0.025; Cox-regression adjusted for history of cardiovascular events). Conclusion. Coronary outpatients with satisfactory medication adherence had lower risk of cardiovascular events over the 24-month monitoring period.